Macleod's clinical diagnosis - Japp, Alan; Robertson, Colin (Colin Ernest); Wright, Rohana J.; Reed, Matthew J.; Robson, Andrew (Andrew J.) (Elsevier, 2018)
Macleod's Clinical Diagnosis demonstrates how to apply the core clinical skills learned from the companion textbook Macleod's Clinical Examination to maximum advantage. Charting the course from routine work-up to diagnosis, this book presents a modern and realistic approach to clinical assessment and explains how to integrate information obtained from the history, examination, bedside tests and specialised investigations